Optimalisasi Kunjungan Posyandu Balita Melalui Program Inovasi Pokban Dan Posyandu Ceria di Rw 8 Kelurahan Karangroto, Kecamatan Genuk, Kota Semarang - Hanifatur Rosyidah; Fifiana Lisani; Ikha Himatul Ulya; Ikliyla Fitri; Khuzaimah Adinda; Risa Febriyani; Zulfa Nursyinta A (Yayasan Daarul Huda Kruengmane, 2023)
Posyandu is a social institution that functions as basic social services and other services according to the potential of each region. Advocacy activities for the head of the posyandu aim to bring the posyandu closer to residents, increase visits by mothers who bring toddlers to the posyandu with a target of 90% success, but coverage has not yet reached the target. Posyandu for toddlers in RW 8 KelurahanKarangroto has been formed, but based on the survey results it was found that the cause of the problem regarding monitoring the growth and development of toddlers is the lack of attitudes and behavior of the mother which is supported by the long distance of the posyandu. The aim of this activity is to increase the coverage of posyandu in RW 8, Karangroto Village, Genuk District, Semarang City. The activity was carried out in RW 8 Karangroto Village, Semarang City with the target of mothers with children under five years of age. The form of activity is